Management and therapeutic implications of combined protein C and S deficiency in pregnancy: a case report - Agrawal, Neha; Ghuman, Navdeep; Singh, Pratibha; Kathuria, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The pregnancy is an immunocompromised state. Thus, autoimmune diseases may affect pregnancy and get worsen during pregnancy. Here authors discuss a rare autoimmune thrombophilia disorder, protein C and S deficiency which may cause recurrent pregnancy losses by affecting haemostatic mechanisms in the body. This patient with recurrent pregnancy loss when evaluated extensively was found to have combined inherited protein C and S deficiency. It was successfully managed with thromboprophylaxis therapy, which resulted in the delivery of healthy baby. Long term anticoagulant prophylaxis should be considered weighing the risk of bleeding to thrombotic recurrence in such cases. In conclusion, combined protein C and S deficiency and that too presenting as recurrent pregnancy loss is very rare. Thrombophilia screening should be considered in cases of recurrent pregnancy losses. Adequate and appropriate thromboprophylaxis is an important part of the management of pregnant women with inherited thrombophilia.